Kritik Sosial dalam Film Miskin Susah Kaya Susah dan Relevansi Pembelajaran Bahasa Indonesia (SATU Press Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2023)
The aims of this research are (1) to describe the social criticism contained in the film Miskin Susah Kaya Susah, (2) to describe its relevance to learning Indonesian in high school. This study used descriptive qualitative method. The data source comes from the film Poor Susah Rich Susah. Data collection techniques using observation and note-taking techniques. The results of the research show that there are four social criticisms which cover the problems of poverty, population, education, and morals. In addition, the film Miskin Susah Kaya Susah can be used as Indonesian language learning material in SMA Class X1 even semester at KD 3.19 to analyze the content and language of the drama or film that is read or watched. From this it proves that there is relevance to the use of film media for learning Indonesian. The benefits that students get from analyzing social criticism in films are developing sensitivity to problems that occur in their environment.